Pelatihan Pembuatan Aneka Roti Manis dalam Kemasan kepada Siswa SMK Sunan Drajat Jember - Adhamatika, Adhima; Triardianto, Dimas; Sucipto, Adi (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
Bread is food product made from wheat Flour which is processed by fermentation dan baking. Bread is very popular in Indonesia with average per capita consumption of bread arround 1.129 ounces per week on 2020. It showed the potential for bread in Indonesia, no exception in Jember. Bread trainong making was conducted for Vocational High School students to improve their competencies. One of Vocational High School in Jember that was focused on bread developing competencies is SMK Sunan Drajat School. It is a private Vocational Education Institution at the biarding school level which also develops several superior schoolproducts like soy milk, bakpia, donuts, and various of bread products at UD. Insyadi Bakery. To improve the students’s competencies at SMK Sunan Drajat, it was necessary to carry out training on making various packaged of breads to support student’s abilities in facing competency test and also preparing their skill.